1993 International Conference on Parallel Processing - ICPP'93 Vol2 1993
DOI: 10.1109/icpp.1993.84
|View full text |Cite
|
Sign up to set email alerts
|

Experiments With Configurable Locks for Multiprocessors

Abstract: X `Y ba bc ed gf ih bp qp sr th 6u ¨v xw ic y by y V V "d e gf i g h f i ei kj l Eh m nf np oy p rq ts uc "r vh mp r w n g "x yd z V "d e gf i g h f i ei kjg kd z ¨ ¢w g Uw vd mz k g U ge g© xf w i hª ` x vf © «f b¬ gf i nf z ee y f w f id m g ¨w ¨ x yw e kd me ve g f Vd me e nd gz Uf z "e § h g x f o § « g d mz k nf t § x vd ®© «d g gf e £ E m § d nd ¡ g¡ gf ¡ kd ¡ g °d me g «z ¨w d b ± gf i² xi g f 6e f 6d b© «d g¡ d g¡ g ge £ E m § ³© «d m d z ee gw y § f n¦ gw e gz g ¢e g g© «f w t « ®d « e ge g ¢ xz kd ¡ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
1996
1996

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…If the molecules are flexible, like the polymers in the base system, locality efficacy may vary as the simulation proceeds and may even vary from domain to domain within a run. While static decisions about the levels at which to exploit molecular locality may provide satisfactory results, dynamic configuration techniques similar to those explored in [6] may be useful in obtaining the highest performance for a MD simulations.…”
Section: Molecular Locality Exploitationmentioning
confidence: 97%
“…If the molecules are flexible, like the polymers in the base system, locality efficacy may vary as the simulation proceeds and may even vary from domain to domain within a run. While static decisions about the levels at which to exploit molecular locality may provide satisfactory results, dynamic configuration techniques similar to those explored in [6] may be useful in obtaining the highest performance for a MD simulations.…”
Section: Molecular Locality Exploitationmentioning
confidence: 97%
“…On-line lock configuration exploits these changes, thereby continually correcting for potential application program and operating system mismatches [20,211. Two such locking patterns for the TSP queue's mutex lock are shown in Figures 3 and 4, depicting both heavy contention on the lock and substantial changes in lock contention over time.…”
Section: Performance Results Of On-line Lockmentioning
confidence: 99%
“…Sample wait attributes are: timeout and spin-time parameters, list of wait methods, etc. These attribute values implement a spectrum of multiprocessor locks ranging from a pure spin lock to a pure blocking lock [20].…”
Section: Performing On-line Threads Configura-mentioning
confidence: 99%
“…For instance, the usual paging policy provided by most operating systems is simply not appropriate for database applications [30]. Mukherjee and Schwan [22] showed that both spinlocks and blocking locks can provide superior performance under different circumstances. Thus it is important to provide operating system facilities that are appropriate to the application.…”
Section: Introductionmentioning
confidence: 99%